2016
DOI: 10.1016/j.jaut.2016.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy-linked FYVE containing protein WDFY3 interacts with TRAF6 and modulates RANKL-induced osteoclastogenesis

Abstract: Recently, autophagy-related proteins were shown to regulate osteoclast mediated bone resorption, a critical process in autoimmune diseases such as rheumatoid arthritis. However, the role of autophagy-linked FYVE containing protein, WDFY3, in osteoclast biology remains elusive. WDFY3 is a master regulator in selective autophagy for clearing ubiquitinated protein aggregates and has been linked with rheumatoid arthritis. Herein, we used a series of WDFY3 transgenic mice (Wdfy3lacZ and Wdfy3loxP) to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…The deletion efficiency of WDFY3 in macrophages and osteoclasts derived from Wdfy3-cKO mice has been previously described [20]. We observed reduced joint swelling in Wdfy3-cKO mice compared to wild type littermates with serum transfer-induced arthritis suggesting that loss of WDFY3 in myeloid cells leads to a protective phenotype in arthritis.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The deletion efficiency of WDFY3 in macrophages and osteoclasts derived from Wdfy3-cKO mice has been previously described [20]. We observed reduced joint swelling in Wdfy3-cKO mice compared to wild type littermates with serum transfer-induced arthritis suggesting that loss of WDFY3 in myeloid cells leads to a protective phenotype in arthritis.…”
Section: Discussionsupporting
confidence: 69%
“…WDFY4 has been associated with rheumatoid arthritis [26] and systemic lupus erythematosus [8] pathology in human genome-wide association studies (GWAS) studies, and WDFY3 has been detected in RA synovial fibroblasts [18] and osteoclasts [19]. Recently we showed that WDFY3 interacts with TRAF6 in RANKL-induced osteoclastogenesis in the absence of inflammation [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-23R GFP reporter mice crossed on RAG1 background and the Wdfy3 floxed mice were previously described [27],[28],[29]. All mice were used between 8–12 wks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of SQSTM1 ubiquitin-binding domain (UBD) leads to increased osteoclast differentiation and function suggesting that SQSTM1 may regulate osteoclastogenesis via multiple pathways [77]. Interaction of autophagy-related proteins SQSTM1 and WDFY3 has been observed in human osteoclasts [78], and we recently showed that WDFY3 deficient mice (WDFY3 fl/fl LysM Cre + ) show enhanced osteoclastogenesis and RANKL-mediated bone resorption in vitro and in vivo assays via TRAF6 dependent activation of NF-κB [79]. Another autophagy-related protein, optineurin (OPTN) also negatively regulates osteoclastogenesis by modulating NF-κB and IFN-β signaling [80].…”
Section: Autophagy/autophagy-related Proteins In Autoimmune Diseasesmentioning
confidence: 99%